1996
DOI: 10.1097/00007632-199605150-00021
|View full text |Cite
|
Sign up to set email alerts
|

New Anterior Instrumentation for the Management of Thoracolumbar and Lumbar Scoliosis

Abstract: New anterior two-rod system showed excellent correction of the frontal curvature and sagittal alignment with extremely high correction capability of rotational deformities. Furthermore, correction of thoracolumbar kyphosis to physiologic lordosis was achieved. This system provides flexibility of the implant for smooth application to the deformed spine and overall rigidity to correct the deformity and maintain the fixation without a significant loss of correction or implant failure compared with conventional on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
2
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(113 citation statements)
references
References 25 publications
5
99
2
7
Order By: Relevance
“…The proponents of anterior instrumentation have report several strategic differences. The choice of instrumentation can differ in terms of its elasticity or rigidity and can consist of either one [5,8,16,39] or two rods [1,7,13,17,34], possibly associated with cages [7,37]. The stiffness of the two-rod construct decreases the risk of hardware breakage.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The proponents of anterior instrumentation have report several strategic differences. The choice of instrumentation can differ in terms of its elasticity or rigidity and can consist of either one [5,8,16,39] or two rods [1,7,13,17,34], possibly associated with cages [7,37]. The stiffness of the two-rod construct decreases the risk of hardware breakage.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…instrumentation set off a new wave of enthusiasm for its potential use in posterior instrumentation [36], and this was accompanied by a loss of interest in the anterior approach, which we criticized in a somewhat provocative article [2]. Several surgeons then improved the anterior constructs to make them stiffer and more efficient [13,14,16,17,33,37]. But almost simultaneously, pedicular screws were developed: the controversy was fueled anew [26] and is still raging today, for both objective and subjective reasons.…”
Section: S158mentioning
confidence: 99%
“…Kaneda et al [5] reported postoperative disc wedging in patients with TL/L AIS following anterior spinal fusion with Kaneda dual rod instrumentation. The average discwedging angle was 6.6°in patients who underwent a short fusion and 3°in patients where the LEV was included in the fusion at 2-4 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, toggling and pullout of the proximal screw was observed with this system. Other systems such as the Kaneda system have used two rods and therefore two screws per vertebra, in an attempt to prevent screw pullout and increase stability [6]. Such systems are, however, indicated for thoracolumbar or lumbar curve and cannot be applied to the upper thoracic vertebrae, which are too small to accommodate two screws.…”
Section: Discussionmentioning
confidence: 99%